Textual Criticism and Qur'an Manuscripts. - Small, Keith E., 1959- (Lexington Books, 2011)
This book pursues the two main goals of textual criticism concerning ancient texts to the text of the Qur'an: 1) to discern the earliest available form of the text, and 2) to illuminate the consequent history of the text. Keith Small shows that the earliest obtainable text is an early edited form of the Arabic consonantal text, but not the original texts described in Islamic historical sources.